2021
DOI: 10.1002/hep.31258
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen B*14:01 and B*35:01 Are Associated With Trimethoprim‐Sulfamethoxazole Induced Liver Injury

Abstract: Background and Aims Trimethoprim (TMP)–sulfamethoxazole (SMX) is an important cause of idiosyncratic drug‐induced liver injury (DILI), but its genetic risk factors are not well understood. This study investigated the relationship between variants in the human leukocyte antigen (HLA) class 1 and 2 genes and well‐characterized cases of TMP‐SMX DILI. Approach and Results European American and African American persons with TMP‐SMX DILI were compared with respective population controls. HLA sequencing was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 33 publications
1
47
0
1
Order By: Relevance
“…Currently, Li et al identified that HLA-B*14:01 allele is the highest associated HLA with co-trimoxazole (sulfamethoxazole-trimethoprim)-related DILI in European Americans (OR = 9.2), while HLA-B*35:01 is the most associated allele in African Americans ( Li et al, 2021 ). In the recent research using the GWAS study, Nicoletti et al discovered that HLA-A*33:01 is associated with DILI, especially with terbinafine-induced liver injury (OR = 40.5) ( Nicoletti et al, 2017 ).…”
Section: Genetic Factors Of Severe Adverse Drug Reactionsmentioning
confidence: 99%
“…Currently, Li et al identified that HLA-B*14:01 allele is the highest associated HLA with co-trimoxazole (sulfamethoxazole-trimethoprim)-related DILI in European Americans (OR = 9.2), while HLA-B*35:01 is the most associated allele in African Americans ( Li et al, 2021 ). In the recent research using the GWAS study, Nicoletti et al discovered that HLA-A*33:01 is associated with DILI, especially with terbinafine-induced liver injury (OR = 40.5) ( Nicoletti et al, 2017 ).…”
Section: Genetic Factors Of Severe Adverse Drug Reactionsmentioning
confidence: 99%
“…Trimethoprim-sulfamethoxazole (TMP-SMX) is an antibiotic available in the ISS formulary. Carriage of HLA-B*14:01 has been associated with TMP-SMX drug induced liver injury in European Americans and HLA-B*35:01 may be a risk factor for African Americans ( Li et al, 2021 ). Similarly, HLA-B*15:02, HLA-C*06:02 and HLA-C*08:01 have been associated with TMP-SMX-induced severe cutaneous reactions ( Kongpan et al, 2015 ).…”
Section: The Use Of Medicines In Spacementioning
confidence: 99%
“…HLA-B*57:01 is the main risk factor for flucloxacillin-DILI and HLA-B*57:03 also show correlation ( Nicoletti et al, 2019 ). HLA-B*14:01 was associate with liver injury induced by cotrimoxazole ( Li et al, 2021 ), while HLA-B*35:02 increase the risk of the occurrence of DILI caused by minocycline ( Urban et al, 2017 ). Among antifungal drug, HLA-A*33:01 was significantly correlated with terbinafine induced DILI ( Nicoletti et al, 2017 ).…”
Section: Dili and Gene Polymorphismmentioning
confidence: 99%